Bóg w życiu człowieka w ujęciu Benedykta XVI - Warzeszak, Józef (Warszawskie Studia Teologiczne, 2017)
The difference between the teachings of St. John Paul II and the teachings of Benedict XVI may be described thus: while the Polish Pope focused on the personal human dignity and thus attempted to restore in man the dignity of God’s image, expiated with Christ’s blood, Benedict XVI attempted to demonstrate God’s priority in man’s personal and social life. He very boldly opposed any contemporary trends which replace God with man, demonstrated the harmful consequences of such ideologies and sought God’s primacy in a man’s life. God deserves that central position, as He is the Creator of man, sustains man’s life and actions, is close to man through Jesus Christ and through the Church, introduces man into the communion of life with Him and constitutes the ultimate fulfilment of human life. As such, the subject discussed appears to be an important element of the teachings of Benedict XVI, as well as an important part of every man’s life.